Analisis Penerapan Risiko Operasional Dan Kepatuhan Syariah Badan Wakaf Al-Qur’an Ditinjau Dari Waqf Core Principles - Sakum; Neng Wiwi; MH Ainulyaqin; Sarwo Edy; Listian Indriyani Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
ABSTRACT. Operational Risk and Sharia Compliance are indicators contained in the waqf Core Principles, which have been applied by the Bekasi Branch Al-Qur’an Waqf Board in minimising operational risks that will occur and indications of sharia compliance. The Waqf assets issued by the Al-Qur’an Waqf Board to the public are Al-Qur’an mushaf, where the waqif donates by giving a sum of money will be used for all operational purposes from collecting money, printing, storing and distributing Al-Qur’an throughout the country. This study aims to analyse the application of Operational Risk and analyse of Sharia Compliance at the Bekasi Branch of the Al-Qur’an Waqf Board. This method with descriptive research and field research. Data collection is carried out by observation and interview process. The results showed that: From six indicators of Operational Risk and from ten indicators of Sharia Compliance, the Al-Qur’an Waqf Board has implemented all of them based on the Waqf Core Principles.